Insider Insights : Building a Results-Based Management and Evaluation System in Colombia - Castro, Manuel Fernando (World Bank, Washington, DC, 2017)
During the past two decades Colombia has been developing and improving its National Results-Based Management and Evaluation System (SINERGIA). The development of this system has been a focal point in Colombia's state reform towards performance-based management, particularly at the central administration. After 15 years of progress, overcoming the effects of institutional, political, and fiscal obstacles, SINERGIA has achieved one of the highest levels of development and customization, and it is held up as an example of best practices by multilateral organizations, donor agencies, and other governments. The monitoring and evaluation (M&E) system that Colombia adopted sought to promote a results focus on both planning and budgeting processes, simultaneously. However, during implementation the results-based planning model superseded the budgeting model, owing principally to the architecture of Colombia's central administration and to the institutional placement of SINERGIA within the Department of National Planning. Compared with similar experiences in other countries, the process by which SINERGIA advanced institutionalization is notable for the way it combined high-ranking, wide ranging, and formal mechanisms with the development of informal practices in key areas of the public sector. Many lessons for other countries are identified in this paper. Some of the key factors in Colombia's success are as follows: 1) the importance of having a central governmental department act as a champion supporter, and using an opportunistic approach to include the M&E system as a key pillar on public sector reform agendas; 2) the kind of regulatory and incentives framework on which the M&E system is based, and the sustained effort in promoting 'cultural' change and developing evaluation capacities; 3) the political role of the President in the system's institutionalization process; 4) the powerful part that technically defined methodologies and dissemination mechanisms have played in the system's institutionalization strategy; 5) the collaborative approach used to strengthen evaluation practices and to enhance the community of evaluators; and 6) the demand-driven approach for introducing M&E at the regional level.